ANALISIS PENGARUH VARIABEL MAKRO EKONOMI DAN REKSADANA TERHADAP INDEKS SAHAM SYARIAH PADA JAKARTA ISLAM INDEKS (JII) - Lia Vebrina Siregar (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2018)
The JII stock index lagged far behind the ISSI stock index which was issued far after JII. The JII stock index can be influenced by inflation, the BI Rate and mutual funds. The method used in this study is analysis using VaR. At the root root test to four stationary data at the 1st difference level so that the test can be continued using VECM. The data used is the time series between January 2012 - December 2017. In the long and short term, JII shares are influenced by mutual funds of -1.84318%. and likewise the prediction of the next 10 years of Shari'ah JII shares will affect Shari'ah mutual funds to reach 42% while the shares are only affected by the shares themselves up to 95 - 96%. Keywords: JII, inflasi, BI Rate, Mutual Funds.